Penerapan Model Pembelajaran Cooperative Learning Tipe Make A Match Untuk Meningkatkan Hasil Belajar Siswa Kelas VIIB SMPN 13 Pontianak - Rosi Desfitri; Titin; Andi Besse Tenriawaru (Jurnal Biogenerasi, 2026)
The study aimed to improve student learning outcomes through the implementation of the cooperative learning model of the make a match type. This research was a classroom action study conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The findings show an improvement in the implementation of the learning process, increasing from 97.05% in the first cycle to 100% in the second. In addition, student learning mastery improved from 76.19% to 85.71%. Based on these results, it can be concluded that the cooperative learning model of the make a match type effectively enhances student learning outcomes in the subtopic of interactions among components of an ecosystem.